Laccase assay based on electrochemistry and fluorescence detection via anthracene sequestered poly(amic acid) films - Esen, Elif; Yazgan, Idris; Demirkol, Dilek Odaci; Timur, Suna (Elsevier BV, 2018)
Abstract Phenols are among the most problematic organic compounds, which manipulates metabolism of living organisms and pose threat to environment. Detection of total phenol at the lowest allowable concentration is critical, so development of sensitive and easy to use methods have been heavily investigated. Hereby, for the first time, anthracene (Ant) was sequestered into poly(amic acid) (PAA) to form fluorescent and conductive film support for laccase (Lac) immobilization to quantify total phenol content at high specificity and selectivity. Ant-PAA/Lac films were applied to fluorescent and electrochemical quantification of phenol, which provided high sensitivity (LOD 46 μM) and reproducibility (RSD, 0.5%) for the tested 10 phenolic compounds including phenol, catechol, 3-acetominophenol, hydroquinone, L-DOPA, 2,6-dimethylphenyl, syringalzadine, 3,5-dimethoxy-4-hydroxycinnamic acid, 2,5-dimethoxyaniline and guaiacol. The sensor system showed strong rejection to common organic interferent while real sample application revealed the applicability of the sensor. Therefore, the results can call the sensor system, particularly fluorescence-based quantification in 96-well plate, is an alternative approach for high-throughput screening of total phenolic compounds in waste-water at cost-effective manner.
Keywords: Electrochemical sensing; Laccase; Fluorescence sensing; Phenol detection; Poly (amic acid) films